Enzimas de biotransformação em tilápia (Oreochromis niloticus) exposta ao hormônio natural 17b-estradiol - Bitencourt, Franciele; Frighetto, Rosa T. S.; Queiroz, Julio F. de; Losekann, Marcos E.; Luiz, Alfredo J. B.; Almeida, Eduardo Alves de [UNESP]; Palhares, Júlio César P. (My University, 2011)
Among the sexual hormones the estrogens are receiving major attention due to their biological activity. Such biological response is atributed to the best conformation recognized by their receptors, resulting in maximum responses. The estrogens are also considered responsible for most of disruptor´s effects caused by their presence in aquatic ecosystems. The 17β-estradiol hormone is produced by vertebrates during the reproductive phase of their lives and its presence has been detected in superficial waters. The objective of this study was to evaluate the cause-effect of tilapia exposition to the hormone 17β-estradiol through the analysis of biotransformation enzymes in liver and gills, complemented with the quantification of 17β-estradiol and estrone in water samples collected from fish ponds integrated to swine production. The present study was conducted under laboratory conditions, in a randomized experimental design with three levels of 17β-estradiol (E2) (0, 5, 15 µg L-1), with three replicates. After 7 days of exposure time, liver and gills were extracted to analyze three isoforms of cytochrome P450: EROD, BROD, PROD and the activity of Glutathione S-Transferase (GST). The results showed that the EROD activity (CYP1A), normally induced by the metabolism of aromatic compounds, did not present statistical differences among the treatments exposed to E2, what means that the hormone did not induce isoform 1A in fish under these particular experimental conditions. PROD activity was significantly altered in both concentrations, by means of 5 and 15 µg L-1, when compared to control. This result can indicate an important role of PROD on the metabolism of E2 present in water. Regarding to the BROD activity, it could be observed differences statistically significant between control and both groups of treatments. Two or more CYP isoforms can contribute to the metabolism of the same compound, what makes BROD a candidate as a next bioindicator of the exposure to E2 in aquatic ecosystems. Analysis of variance could confirm the effect of E2 statistically significant on the GST activity in liver tissues with >90% of significance (Prob>F = 0.0753). Furthermore, it was possible to observe that the values of GSTs activities in liver and gills in both, control and treatments, follow a tendency, that means, enzymatic activity in gills increase as the increasing of the activity in the liver tissues. In this study, the 17β–estradiol was found in measurable concentrations in three sampled points, and these values were similar to the findings of other authors at different locations in Brazil. In addition, those values are much higher than the minimum concentration that presented observable effects (10 ng L-1).

Dentre os hormônios sexuais, os estrógenos vêm recebendo maior atenção pela atividade biológica que eles apresentam. Essa resposta biológica é atribuída à melhor conformação reconhecida pelos receptores, resultando em respostas máximas. Os estrógenos são também considerados responsáveis pela maioria dos efeitos disruptores desencadeados pela sua presença nos organismos do ecossistema aquático. O hormônio 17β-estradiol é produzido por vertebrados na fase reprodutiva do seu desenvolvimento e sua presença tem sido detectada nas águas superficiais. O objetivo do estudo foi avaliar a causa-efeito da exposição da tilápia ao hormônio 17β-estradiol através da análise de enzimas de biotransformação no fígado e brânquias; complementado com a quantificação de 17β-estradiol e estrona em amostras de águas advindas dos viveiros integrados com a produção de suínos. Este estudo foi conduzido em condições de laboratório, em delineamento totalmente casualizado, com três níveis de concentração do hormônio 17β-estradiol (E2) (0, 5, 15 µg L-1). Após 7 dias de exposição, fígados e brânquias foram extraídos para análise da atividade de três isoformas de citocromo P450: EROD, BROD, PROD e a atividade de Glutationa S-Transferase (GST). Os resultados mostraram que a atividade de EROD (CYP1A), comumente induzida no metabolismo de substâncias aromáticas, não apresentou diferença estatística entre os diferentes tratamentos de E2, indicando que o hormônio não exerce indução desta isoforma nos peixes, nas concentrações e tempo de exposição testados. A atividade da PROD foi significativamente alterada nos dois tratamentos de E2 em comparação ao controle. Esse resultado pode indicar um papel importante desta atividade no metabolismo do E2 presente na água. Com relação à atividade da BROD, pode-se notar que houve diferença estatisticamente significativa entre o controle e os dois grupos tratados com o E2. Pelo fato de duas ou mais isoformas de CYP poderem contribuir para o metabolismo de um único composto, a BROD pode ser considerada como outro biomarcador da presença de 17β-estradiol na água superficial. A análise de variância do experimento confirmou a existência do efeito de E2 estatisticamente significativo sobre a atividade enzimática (GST) nos fígados dos peixes, com grau de significância superior a 90% (Prob>F = 0,0753). Além disso, foi possível observar que os valores das atividades de GSTs das brânquias e fígados dos peixes-controle e tratados seguem uma tendência, isto é, a atividade enzimática das brânquias aumenta conforme o aumento da atividade no fígado. O 17β-estradiol esteve presente em concentrações quantificáveis nos pontos amostrados, estando esses valores dentro das concentrações encontradas por outros autores em outras localidades do Brasil. Esses valores são muito maiores que a concentração mínima para apresentar algum efeito observável (10 ng L-1), descrito em literatura.
Keywords: Biomarcadores; 17β-estradiol; Tilápia; Biomarkers; 17β-estradiol; Tilapia